Copper‐Mediated [(Diethylphosphono)difluoromethyl]thiolation of α‐Bromo Ketones. Issue 17 (3rd May 2017) - Ivanova, Maria V.; Bayle, Alexandre; Besset, Tatiana; Pannecoucke, Xavier; Poisson, Thomas
Abstract : We report herein a straightforward access to α‐[(diethoxyphosphoryl)difluoromethyl]thiolated ketones. The methodology, which involves the nucleophilic [Cu]CF2 PO(OEt)2 species, has allowed the formation of the targeted compounds in moderate to high yields by using a simple procedure. This method represents a convenient alternative to the known approaches for the introduction of this emergent fluorinated motif. Abstract : The synthesis of α‐[(diethylphosphono)difluoromethyl]thiolated ketones starting from the corresponding α‐bromo ketones is reported. By using the nucleophilic [Cu]CF2 PO(OEt)2 species prepared from CuSCN, the thiolated ketones were obtained in moderate to high yields using a simple procedure.